Philosophy Positivism Law In Implementation Law In State Of Emergency - Fathiya Firdiansyah Putri (Fakultas Hukum Universitas Lampung, 2026)
This study examines how legal positivism justifies the implementation of law during states of emergency and how constitutionalism limits emergency powers to prevent abuses of authority. Using normative legal research, it analyzes legislation, legal principles, doctrines, theories, and relevant literature concerning the validity of emergency measures within the Indonesian legal system. Legal positivism conceives law as a system of norms enacted and enforced by legitimate authorities, irrespective of moral considerations. Hans Kelsen's theory of hierarchical norms suggests that emergency measures are legally valid only when they derive from higher legal norms and are adopted through prescribed legal procedures. The study finds that legal positivism provides a formal basis for rapid state action during emergencies but is inadequate without constitutional constraints. Accordingly, emergency powers must remain subject to the 1945 Constitution, human rights protections, proportionality, temporal limitations, and checks and balances. The study recommends strengthening Indonesia's emergency law framework through clearer regulations, greater transparency, and more effective constitutional oversight to prevent arbitrary exercises of power during crises.